Antimicrobial Effect Of Honey Distributed Around Pasar Minggu Jakarta Selatan - Ruth Elenora Kristanty; Junie Suriawati; Priyanto Dwi Nugroho (Politeknik Kesehatan Kemenkes Jakarta II, 2017)
Honey is a highly nutritious food product and consumed by almost all the population in the world. It has a function as an antimicrobial. Staphylococcus aureus (S. aureus) is a common Gram-positive bacteria in food and Escherichia coli (E. coli) is a Gram-negative bacteria that often appears in environmental sanitation issues that both can cause infectious diseases. Some infectious diseases can be treated with antimicrobials such as honey. The purpose of this study was to test the antimicrobial effects on honey products distributed in Pasar Minggu area. The antimicrobial effect test was performed in vitro using agar diffusion method by measuring the inhibition zone formed where the bacteria growth was inhibited by the presence of sample. The concentration of samples were 25%, 50%, 75%, and 100% (not diluted) and as aquades control. The results showed that honey tested with various dilution concentrations resulted inhibition zone and. The higher concentration of the inhibited zone zone showed antimicrobial activity against S. aureus and E. coli.